Readiness to change and deception as predictors of program completion in perpetrators of intimate partner violence - McDonagh, Tracey (Journal of family violence, 2025)
Purpose: Intimate partner violence (IPV) is a global problem with severe health and human rights implications. However, prevention of IPV recidivism has proved difficult, with high levels of treatment non-adherence including failure to complete IPV perpetration programs. Method: The present study involved gathering data from the records of 169 men convicted of perpetrating intimate partner violence in Northern Ireland. Using a hierarchical binary logistic regression, motivation/readiness to change, as measured by the pre-contemplative stage of the Rhode Island Change Assessment Scale (URICA), was investigated as a predictor of IPV intervention program completion. The analysis also included deception covariates (self-deception and impression management). Results: The results show that higher scores on the pre-contemplative subscale of the readiness to change scale were significantly associated with failure to complete the program, with an odds ratio of OR 0.93 (inverted OR = 1.08). The covariate self-deception was also significant in the final model, with higher scores in self-deception leading to an increased chance of non-completion, with an odds ratio of 0.89 (inverted OR = 1.12). A post-hoc Chi-Square test was carried out that showed treatment completers were less likely than non-completers to breach their probation conditions χ2(1, n = 148) = 69.85, p =  < 0.001. Conclusion: Due to the potentially positive impact of completing an intervention program for IPV perpetrator outcomes, the present study is important in terms of indicating that motivational stage, as well as self-deception, are relevant to treatment compliance. This finding suggests that targeting areas such as treatment readiness and self-deception may lead to improved treatment adherence and IPV perpetrator rehabilitation.